EFFECTIVE USE OF ASSETS IN THE CORPORATE GOVERNANCE SYSTEM (Web of Discoveries: Journal of Analysis and Inventions, 2023)
This article is devoted to improving the methodological tools in choosing the effective use of enterprise assets in the corporate governance system.